Comparison of Mandibular Volume and Linear Measurements in Patients with Mandibular Asymmetry - Yuki Hikosaka; So Koizumi; Yong-Il Kim; Mohamed Adel; Mohamed Nadim; Yu Hikita; Tetsutaro Yamaguchi (Diagnostics, 2023)
In patients with mandibular asymmetry, the volume of the mandible divided by the mandibular median plane is significantly larger on the non-deviated (N-Dev) side than on the deviated (Dev) side. However, it has been reported that there is no significant difference between the volumes of the N-Dev and Dev sides when the mandibular ramus and body are divided. The purpose of this study was to investigate which region is responsible for the volume difference between the N-Dev and Dev sides. Cone Beam Computed Tomography (CBCT) images of patients with mandibular asymmetry were analyzed by measuring the volume, and linear analysis of the mandibular body, ramus, and condyle on the N-Dev and Dev side was performed. In this study, CBCT images of 37 patients (8 Japanese, 16 Korean, and 13 Egyptian) aged ≥ 18 years with mandibular asymmetry (men: 20, women: 17) were used to evaluate mandibular asymmetry. In patients with mandibular asymmetry, the N-Dev side showed significantly larger values than the Dev side for both volume and linear condyle, ramus, and mandibular body measurements. These results do not differ according to sex or ethnicity. Therefore, it is suggested that the N-Dev side of mandibular asymmetry is large without any regional specificity in pathophysiology.